THE ROLE OF TOPOGRAPHY AND LATENT HEAT IN THE VORTEX DEVELOPMENT OVER EASTERN INDIAN OCEAN - Putri Damayanti, Riggita
Development of the vortex is associated with topographical effects and latent heat release. Topography and latent heat can affect the stability of the atmosphere and have the potential to cause disturbances, such as vortices. This study aims to analyze the role of both of them to vortex formation. This research investigates six case studies of vortex development in the Eastern Indian Ocean using an energy budget to analyze the vortex development and the mechanism of vortex formation is further analyzed by means of numerical simulations. The data used is NCEPFNL. The results showed that the vortex in the Eastern Indian Ocean is associated with an imbalance that starts from the lower level, causing disturbances as indicated by the presence of negative vortices and vortices forming. In numerical simulations that play the role of topography and latent heat, it shows that the role of Sumatra's topography is more dominant for vortex formation. When the simulation is run with reduced topography, the results show that no vortices are formed. On the other hand, the release of latent heat plays an important role in the intensification and development of these lower level vortices.